Rimegepant 75 mg for acute treatment of migraine is associated with significant reduction in monthly migraine days: Results from a long-term, open-label study. (31st January 2022) - L'Italien, Gilbert; Popoff, Evan; Johnston, Karissa; McGrath, Donnie; Conway, Charles M; Powell, Lauren; Harris, Linda; Kowalczyk, Nicole; Croop, Robert; Coric, Vladimir
Background: Rimegepant, a small molecule oral calcitonin gene-related peptide (CGRP) receptor antagonist, is approved for the acute and preventive treatment of migraine. We hypothesized that intermittent CGRP receptor blockade with rimegepant 75 mg acute treatment as needed (PRN) might result in reductions in monthly migraine days (MMD) over time, and was evaluated as the study objective. Methods: This was a post-hoc analysis of adults with ≥6 MMD at baseline who self-administered rimegepant 75 mg orally PRN for acute treatment of migraine up to 52-weeks in an open-label safety study (BHV3000-201; NCT03266588). Outcome measures (defined as median time to) and response rates (defined as proportion of patients reporting) were captured for ≥30% and ≥50% reduction of baseline MMD. Results: 1044 participants with ≥6 MMD at baseline were analyzed. Median time to ≥30% reduction in MMD was 12 weeks (IQR; 4–40 weeks); median time to ≥50% reduction was 32 weeks (IQR; 12-NR weeks). Reduction in MMD was observed over time regardless of baseline migraine frequency, however higher baseline MMD were associated with a longer time to achieving ≥30% or ≥50% MMD reduction. Conclusion: In participants presenting with ≥6 MMD, PRN acute treatment of migraine attacks over 52-weeks with oral rimegepant 75 mg was observed to confer reductions in migraine frequency. Trial registration: NCT03266588